Influence of grain boundaries on elasticity and thermal conductivity of nanocrystalline diamond films. (1st January 2017) - Mohr, Markus; Daccache, Layal; Horvat, Sebastian; Brühne, Kai; Jacob, Timo; Fecht, Hans-Jörg
Abstract: Diamond combines several outstanding material properties such as the highest thermal conductivity and highest elastic moduli of all materials. This makes diamond an interesting candidate for a multitude of applications. Nonetheless, nanocrystalline diamond films, layers and coatings, usually show properties different to those of single crystalline diamond. This is usually attributed to the larger volume fraction of the grain boundaries with atomic structure different from the single crystal. In this work we measured Young's modulus and thermal conductivity of nanocrystalline diamond films with average grain sizes ranging from 6 to 15 nm. The measured thermal conductivities are modeled considering the thermal boundary conductance between grains as well as a grain size effect on the phonon mean free path. We make a comparison between elastic modulus and thermal boundary conductance of the grain boundaries G k for different nanocrystalline diamond films. We conclude that the grain boundaries thermal boundary conductance G k is a measure of the cohesive energy of the grain boundaries and therefore also of the elastic modulus of the nanocrystalline diamond films. Graphical abstract: Image 1